Efek Mengkonsumsi Minuman Beralkohol Terhadap Kadar Triglisrida - Dwi Purbayanti; Nur Aryanti Rembulan Saputra (Jurnal Surya Medika (JSM), 2017)
Heavy drinkers who consume more than 30 grams of alcohol per day will increase the risk of increasing triglyceride levels. Chronic ethanol metabolism causes disrupted fatty acid oxidation and the transfer of carbon to fat causes an increase in the production of triglycerides in the liver. The excess triglycerides in the liver are then removed from the blood vessels and there is a buildup of triglycerides in the blood vessels and can progress to Coronary Heart Disease (CHD). This study aims to describe the triglyceride levels in alcohol users on Jalan Mendawai, Palangka Raya City. This study uses a descriptive method to describe triglyceride levels in people who use or consume alcohol on Jalan Mendawai, Palangka Raya City. The number of samples obtained were 20 samples and taken using purposive sampling technique, with criteria that are male sex, more than 20 years old, had consumed alcohol more than 5 years, at least 1 time in 1-week consuming alcohol and willing to be sampled. The results showed that only 1 person (5%) had normal triglyceride levels and 19 people (95%) had normal triglyceride levels. Based on the criteria for the risk of coronary heart disease (CHD) that is 1 person (5%) had triglyceride levels with ideal criteria, 4 people (20%) included in the criteria for high risk of CHD risk, 7 people (35%) which included high-risk criteria and 8 people (40%) which included very high-risk criteria for CHD.